IMPROVING EMPLOYEE PERFORMANCE THROUGH WELFARE INITIATIVES AND MANAGERIAL ROLES: A CASE STUDY OF PT ASURANSI SINARMAS, CENTRAL JAKARTA, CREDIT CONTROL DIVISION - Agrasadya, Agrasadya; Sunarto, Ading (Yayasan Education and Social Center, 2026)
This study aims to understand how employee welfare programs and managerial roles contribute to performance improvement in the Credit Control Division of PT Asuransi Sinarmas, Central Jakarta. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observations, and documentation studies. The research focuses on employees' experiences with welfare program benefits and their perceptions of leadership style and managerial support. The findings indicate that welfare programs encompassing health, financial, and work–life balance aspects enhance employee motivation, loyalty, and productivity. Furthermore, managerial roles demonstrated through open communication, clear guidance, and recognition of employee achievements strengthen work engagement and organizational commitment. Welfare programs and managerial roles create a conducive work environment, thereby enabling sustainable performance improvement in the Credit Control Division. This study emphasizes that performance improvement does not solely depend on targets and control systems, but also on holistic support for employee welfare and the quality of managerial leadership. These findings are expected to provide strategic input for the company in designing more effective and sustainable human resource policies.